Solitons in crystalline processes : irreversible thermodynamics of structural phase transitions and superconductivity - Fujimoto, Minoru (IOP ebooks. 2020 collection., 2020)
Solitons play a fundamental role in ordering processes in crystals. In the first edition, the essential mechanism of structural changes where solitons play the fundamental role of boson statistics was detailed for irreversible thermodynamics in crystals; explaining not only structural transformations and mesoscopic disorder, but also the nonlinear mechanism of superconductivity. A major development and extension presented in this new edition is in the application of soliton theory to polymers and liquid crystals, in addition to capturing both theoretical developments and newer experimental results of soliton analysis in general. This new edition also emphasises the thermodynamics of soft modes, pseudospins and order variables for finite lattice displacements. The soliton statistics of the nonlinear order variables are logically discussed.